Cardiovascular Autonomic Responses to Aerobic, Resistance and Combined Exercises in Resistance Hypertensive Patients. (20th April 2022) - Fraccari-Pires, Nayara; Coelho-Júnior, Hélio José; Gambassi, Bruno Bavaresco; Cabral de Faria, Ana Paula; Ritter, Alessandra Mileni Versuti; Gasparetti, Carolina Souza; Pioli, Mariana Rodrigues; Ruberti, Olívia Moraes; Ferreira-Melo, Silvia Elaine; Moreno, Heitor; Rodrigues, Bruno
Abstract : Here, we report the acute effects of aerobic (AER), resistance (RES), and combined (COM) exercises on blood pressure, central blood pressure and augmentation index, hemodynamic parameters, and autonomic modulation of resistant (RH) and nonresistant hypertensive (NON-RH) subjects. Twenty participants (10 RH and 10 NON-RH) performed three exercise sessions (i.e., AER, RES, and COM) and a control session. Hemodynamic (Finometer®, Beatscope), office blood pressure (BP), and autonomic variables (accessed through spectral analysis of the pulse-to-pulse BP signal, in the time and frequency domain-Fast Fourrier Transform) were assessed before (T0), one-hour (T1), and twenty-four (T2) hours after each experimental session. There were no changes in office BP, pulse wave behavior, and hemodynamic parameters after (T0 and T1) exercise sessions. However, AER and COM exercises significantly reduced sympathetic modulation in RH patients. It is worth mentioning that more significant changes in sympathetic modulation were observed after AER as compared to COM exercise. These findings suggest that office blood pressure, arterial stiffness, and hemodynamic parameters returned to baseline levels in the first hour and remained stable in the 24 hours after the all-exercise sessions. Notably, our findings bring new light to the effects of exercise on RH, indicating that RH patients show different autonomic responses to exercise compared to NON-RH patients. This trial is registered with trial registration number NCT02987452 .